2012
DOI: 10.1007/s12630-012-9779-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sonoanatomy relevant to performing stellate ganglion blocks using anterior and lateral simulated approaches: an observational study

Abstract: Purpose Stellate (cervicothoracic) ganglion block (SGB) can be associated with serious complications, such as esophageal and vascular injury. The objective of this study was to evaluate the potential for vascular and esophageal injury in healthy subjects by examining the sonoanatomy of the neck relevant to the SGB at the sixth (C6) and seventh (C7) cervical vertebral levels and determining the incidence of blood vessels and esophagi in the simulated path of needle insertion in the conventional and two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…5,6 However, identification of small vessels is often difficult, even by ultrasonography, because of the anatomical relation with the thyroid gland and the complex courses of the blood vessels. 7,8 Three-dimensional computed tomography (3D-CT) with contrast medium was recently introduced. This imaging modality allows identification of obscure blood vessels in the head and neck region.…”
mentioning
confidence: 99%
“…5,6 However, identification of small vessels is often difficult, even by ultrasonography, because of the anatomical relation with the thyroid gland and the complex courses of the blood vessels. 7,8 Three-dimensional computed tomography (3D-CT) with contrast medium was recently introduced. This imaging modality allows identification of obscure blood vessels in the head and neck region.…”
mentioning
confidence: 99%
“…Although the vertebral artery enters the foramen transversarium at the level of C6 by which it is wellseparated from the stellate ganglion, anatomical variations are known to occur and in one of the studies, the vertebral artery was lying outside the foramen transversarium in up to 7% of the cases. 10 Studies have shown that injection of even a minimal dose of the local anesthetic into the vertebral artery can cause seizures as the injected local anesthetic directly reaches the brain.…”
Section: Relation Of the Vertebral Artery To The Stellate Ganglionmentioning
confidence: 99%
“…The chances of encountering a major vessel is high with anterior approach at C7 level than at C6 level (29 and 43% respectively). 10 On the left side, the esophagus was located along the needle path in 39 of 60 cases at C7 level as compared to 22 of 60 cases at C6 level. 13 These above mentioned observations make the block at C6 more favorable.…”
mentioning
confidence: 91%
“…Injury to the esophagus, thyroid gland, thyroidal arteries and vertebral artery is a legitimate risk with both techniques [61,62]. US-guided SGB uses a medial or lateral approach [63]. The medial technique increases the chance of trauma to the esophagus and thyroidal arteries; therefore, we prefer a lateral in-plane approach which allows the needle to pass lateral and posterior to the carotid artery and anterior to Chassaignac's tubercle (Figure 10).…”
Section: • Stellate Ganglion Blockmentioning
confidence: 99%
“…US-guided SGBs are more accurate (as determined by resultant Horner's syndrome) as compared with the landmark technique (100 vs 80-90%) [63]. Sonography is associated with fewer complications such as organ injury or Ultrasound-guided interventional procedures for chronic pain management REviEW future science group www.futuremedicine.com hematoma [61].…”
Section: • Stellate Ganglion Blockmentioning
confidence: 99%